Low-Temperature Electrospinning-Fabricated Three-Dimensional Nanofiber Scaffolds for Skin Substitutes - Qiqi Dai; Huazhen Liu; Wenbin Sun; Yi Zhang; Weihuang Cai; Chunxiang Lu; Kaidi Luo; Yuanyuan Liu; Yeping Wang (Micromachines)
Severe skin damage poses a significant clinical challenge, as limited availability of skin donors, postoperative skin defects, and scarring often impair skin function. Traditional two-dimensional (2D) nanofibers exhibit small pore sizes that hinder cellular infiltration, unable to simulate the three-dimensional (3D) structure of the skin. To address these issues, we developed 3D porous nanofiber scaffolds composed of polycaprolactone–polylactic acid–mussel adhesive protein (PLGA-PCL-MAP) using low-temperature electrospinning combined with nano-spray technology. Meanwhile, this 3D scaffold features high porosity, enhanced water absorption, and improved air permeability. The incorporation of mussel adhesive protein (MAP) further increased the scaffold’s adhesive properties and biocompatibility. In vitro experiments demonstrated that the 3D nanofiber scaffolds significantly promoted the adhesion, proliferation, and migration of epidermal keratinocytes (HaCaTs) and human fibroblasts (HFBs), while providing ample space for inward cellular growth. Successful co-culture of HaCaT and HFBs within the scaffold revealed key functional outcomes: HaCaTs expressed keratinocyte differentiation markers CK10 and CK14, while HFBs actively secreted extracellular matrix components critical for wound healing, including collagen I, collagen III, and fibronectin. This skin substitute with a composite structure of epidermis and dermis based on three-dimensional nanofiber scaffolds can be used as an ideal skin replacement and is expected to be applied in wound repair in the future.